2013
DOI: 10.1002/ccd.24404
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter therapy for aortic coarctation with severe systemic hypertension during pregnancy

Abstract: Aortic coarctation is an unusual cause of hypertension during pregnancy and its management is not clarified. We report transcatheter balloon dilatation and stenting for native aortic coarctation in a 22-year-old pregnant woman with severe and uncontrolled systemic hypertension. Arterial blood pressure could be successfully controlled with medical treatment during the rest of the pregnancy and the patient underwent uneventful delivery. No adverse events or recoarctation was observed during 24 months clinical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
0
15
0
4
Order By: Relevance
“…Rest of the pregnancy of their patient was uneventful [9]. They pointed out a need for randomized trials for confirming the safety of stenting during pregnancy [9]. Our patient's blood pressure remained high after stenting and she even needed antihypertensives.…”
Section: Internal Medicine Section Abstractmentioning
confidence: 69%
See 2 more Smart Citations
“…Rest of the pregnancy of their patient was uneventful [9]. They pointed out a need for randomized trials for confirming the safety of stenting during pregnancy [9]. Our patient's blood pressure remained high after stenting and she even needed antihypertensives.…”
Section: Internal Medicine Section Abstractmentioning
confidence: 69%
“…Zeira and Zohar reported 2 pregnant women with coarctations who were also medically followed-up until their deliveries [8]. However, Assaidi et al, reported a case in which they had implanted a stent for coarctation of aorta during pregnancy, without complications [9]. Rest of the pregnancy of their patient was uneventful [9].…”
Section: Internal Medicine Section Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled hypertension may lead to neonatal and maternal adverse events [3]. Percutaneous treatment of severe coarctation with uncontrolled hypertension has been described during pregnancy [4]. However, in our patient, medical therapy successfully controlled the hypertension, allowing interventional therapy to be postponed until after delivery, and avoiding the use of radiation and general anesthesia during pregnancy.…”
Section: Commentmentioning
confidence: 71%
“…It is known that aortic disease is more aggressive during pregnancy. The mechanism includes increased wall stress from hyperdynamic cardiovascular changes, particularly from 12 to 28 weeks gestation, and oestrogen-induced aortic media degeneration [ 1 , 3 ]. Sometimes, adult CoA may be first diagnosed during pregnancy, necessitating emergency surgery [ 1 ], as in the present case.…”
Section: Discussionmentioning
confidence: 99%